Plan de negocio para la comercialización de un Tripack nutricional de productos lácteos, cantón Quevedo, año 2014 - Arellano Cisneros, Edison Patricio (2015)
This study seeks to satisfy unmet City Quevedo, by designing a business plan to implement a marketer of a triple pack of the same nutritional dairy products including cheese, yogurt and milk, for this fu necessary make a contextualization of the problems that allowed defining specific objectives that helped the development of research. The business plan was developed through a market study helped identify existing dairy supply and demand of the population which satisfy a new agile and innovative product with nutritional characteristics that benefit consumers who purchase such pack dairy. He proceeded to prepare a technical study was to identify the business and all the rigorous process to be followed so that the product reaches the end consumed. t was necessary to establish the organization of the company by identifying the human resources to work at its marketing , the author of this business plan consider it important to conduct an economic study reference and current suppliers of machinery prices, technological equipment to be used this allowed to develop a study to determine the financial viability of the investment with a net present value of $ 231,733.21 , the internal rate of return exceeded that required by the current market 48 %, while the cost-benefit ratio showed that the project is feasible its implementation with a current benefit of 6.93 .